2023
DOI: 10.1021/acs.analchem.3c02246
|View full text |Cite
|
Sign up to set email alerts
|

Differential Correlations Informed Metabolite Set Enrichment Analysis to Decipher Metabolic Heterogeneity of Disease

Genjin Lin,
Liheng Dong,
Kian-Kai Cheng
et al.

Abstract: Metabolic pathways are regarded as functional and basic components of the biological system. In metabolomics, metabolite set enrichment analysis (MSEA) is often used to identify the altered metabolic pathways (metabolite sets) associated with phenotypes of interest (POI), e.g., disease. However, in most studies, MSEA suffers from the limitation of low metabolite coverage. Random walk (RW)-based algorithms can be used to propagate the perturbation of detected metabolites to the undetected metabolites through a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, given the limitation of analytical platforms and the wide diversity of metabolites in physicochemical properties, routine detection-based metabolomics approaches are not always able to capture disease-related functional core metabolites. More recently, approaches in computational network biology, such as controllability or propagation analysis, have been demonstrated as efficient tools for extracting key information from complex biological associations. These studies showed a promising perspective of the network-based approach in the discovery of key metabolites, especially for evaluating the influence of undetected metabolites on regulatory function of metabolic pathways . Therefore, there is an unmet need for an adaptable methodology to integrate detection-based metabolomics and network-based approaches, allowing researchers to identify functional core metabolites that have critical guiding meaning for disease diagnosis and drug treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, given the limitation of analytical platforms and the wide diversity of metabolites in physicochemical properties, routine detection-based metabolomics approaches are not always able to capture disease-related functional core metabolites. More recently, approaches in computational network biology, such as controllability or propagation analysis, have been demonstrated as efficient tools for extracting key information from complex biological associations. These studies showed a promising perspective of the network-based approach in the discovery of key metabolites, especially for evaluating the influence of undetected metabolites on regulatory function of metabolic pathways . Therefore, there is an unmet need for an adaptable methodology to integrate detection-based metabolomics and network-based approaches, allowing researchers to identify functional core metabolites that have critical guiding meaning for disease diagnosis and drug treatment.…”
Section: Introductionmentioning
confidence: 99%